Neutropenia in patients with inflammatory arthritis treated with sulphasalazine. Issue 9 (September 1986) - Farr, M; Symmons, D P; Blake, D R; Bacon, P A
Abstract : This report describes two patients who developed severe neutropenia one month after starting sulphasalazine (SASP) as treatment for their inflammatory joint disease. Both recovered on stopping the drug. Six further cases (out of a series of 180 patients with inflammatory forms of arthritis receiving SASP therapy) in whom transient leucopenia occurred are also recorded. These patients were able to continue the drug under close supervision. Sulphasalazine is a useful addition to the small number of slow acting antirheumatic drugs (SAARDs) and, despite this complication, is safer than other SAARDs. Careful monitoring of patients is essential, however, particularly in the early stages of treatment, to detect this adverse reversible reaction promptly.